2019
DOI: 10.1111/odi.13248
|View full text |Cite
|
Sign up to set email alerts
|

Persistent dentoalveolar pain disorder: A putative intraoral chronic overlapping pain condition

Abstract: Chronic pain is considered a major health issue affecting around 20% of people worldwide and being accounted for 15%-20% of all medical visits (Treede et al., 2015). Chronic pain significantly impacts patients' well-being and quality of life, affecting their mood, coping resources, expectations, sleep quality, and physical function. Moreover, it is highly associated with disability and suicidal risk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Part of the clinical picture is multifocal pain; co-morbidity between chronic pains is frequent. In line with this, PIDAP was recently proposed to be a chronic overlapping pain condition (COPC) (48) although this attribution needs more clinical data. In this context it should be considered that the inconclusive electrophysiological results may also result from the limited field testing of the ICOP criteria as it may be the case that different pathologies lead to the same clinical phenotype.…”
Section: Persistent Orofacial Painmentioning
confidence: 95%
“…Part of the clinical picture is multifocal pain; co-morbidity between chronic pains is frequent. In line with this, PIDAP was recently proposed to be a chronic overlapping pain condition (COPC) (48) although this attribution needs more clinical data. In this context it should be considered that the inconclusive electrophysiological results may also result from the limited field testing of the ICOP criteria as it may be the case that different pathologies lead to the same clinical phenotype.…”
Section: Persistent Orofacial Painmentioning
confidence: 95%
“…Furthermore, the injection of lidocaine to the site of pain only partially relieves spontaneous pain, suggesting a contribution of the central mechanisms of sensitization [ 77 ]. AO is also suggested to be a chronic overlapping pain condition: AO occurs more frequently in females and is often comorbid with other chronic pain conditions, such as temporomandibular disorders (TMD; more frequent in females) or headaches, and emotional disorders, such as depression and anxiety [ 78 ].…”
Section: Pathological Painful Conditions and Underlying Neurobiologymentioning
confidence: 99%
“…One study revealed decreased brain activations in regions of the frontoparietal attention network in TMD patients subjected to forearm heat [24] while another found no brain activation differences between TMD patients and controls in response to thumbnail pressure pain [33]. In a previous sfMRI study done by our group, noxious dentoalveolar pressure stimuli was applied to patients with persistent dentoalveolar pain disorder (PDAP), a chronic orofacial pain condition affecting the dentoalveolar structures [39] which is commonly comorbid with TMD pain [40]. Compared to controls, PDAP patients exhibited a greater extent of brain activations over several brain areas including SI, SII, insula, prefrontal cortex, and thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to controls, PDAP patients exhibited a greater extent of brain activations over several brain areas including SI, SII, insula, prefrontal cortex, and thalamus. Given that 50% of PDAP patients are also diagnosed with TMD [40, 41], these findings raise the possibility that chronic TMD pain patients may also present abnormally amplified brain responses following noxious dentoalveolar pressure stimulation, in a similar fashion to PDAP patients, even though this is not a site commonly reported as painful by that patient population.…”
Section: Introductionmentioning
confidence: 99%